Typology of Contemporary Media Texts: Problems of Identification, Delimitation, Typology - Gazieva Dilfuza (Scholars Digest Publishing, 2023)
The article deals with the media-text as a basic category of media-linguistics, which has universal and unique characteristics. The specific characteristics of media-texts are their mass nature, media, semiotic integrativity, intertextual openness. Typology of media texts is based on eight categories: communication channel, institutional type of text, typological characteristics of an edition or channel, addressee, addressee, code, functional and genre affiliation of texts, thematic dominant.
Keywords: media text, media product, media, media, media discourse, media genres.